Oil Palm Plantation Expansion and Population Problems: An Explanatory Factor for Deforestation in Indonesia - Widiono, Septri (Department of Sociology, Faculty of Social Sciences, Gorontalo State University, Indonesia, 2024)
Deforestation in Indonesia remains a significant issue due to various factors. This article reveals the impact of demographic variables on deforestation, using oil palm plantation expansion as a case study. The study applies Hunter's model, considering population dynamics and intermediate variables, namely science and technology, institutions, policies, and culture. Through traditional literature review methods, demographic data and field research results from 2010 to 2020 were elaborated, focusing on Sumatra, Kalimantan, and Sulawesi. The findings underline that Indonesian rapid population growth drives high consumption rates. Additionally, the development of oil palm plantations is faced with high demand for CPO, policies that attach too much importance to investment, and agrarian deregulation. All these intermediate variables are visible through the agricultural expansion as a pattern of agricultural development. The massive expansion by private companies resulted in a change in the socio-ecological landscape. In addition, there are dilemmas in the villager's livelihood system, such as shifting traditional livelihood bases, livelihood dualism, the emergence of new vulnerabilities, and land grabs. In order to realize sustainable palm oil development, we suggest governance reforms at the global, national, and local levels.